Facile Construction of g‐C3N4 Nanosheets/TiO2 Nanotube Arrays as Z‐Scheme Photocatalyst with Enhanced Visible‐Light Performance. Issue 19 (30th August 2016) - Zhou, Dantong; Chen, Zhi; Yang, Qian; Shen, Cai; Tang, Gao; Zhao, Shilong; Zhang, Jingji; Chen, Da; Wei, Qinhua; Dong, Xiaoping
Abstract: Semiconductor photocatalysis may be a promising strategy to face energy and environmental issues because it utilizes the solar energy as energy source. The artificially Z‐scheme photocatalytic system has attracted special interests owing to its high efficiency and strong redox ability. Graphitic carbon nitride nanosheets (g‐C3 N4 NSs) display prominent performances, which are intensively investigated. Herein, we constructed an all‐solid‐state Z‐scheme photocatalytic system and firstly immobilized g‐C3 N4 nanosheets on TiO2 nanotube arrays (TNTAs) by a simple method. The microstructures of prepared g‐C3 N4 NSs/TNTAs photocatalyst were characterized by XRD, X‐ray photoelectron spectroscopy, SEM and TEM. The features of light absorption, charge separation, and charge transfer were analyzed by UV/Vis diffuse reflectance techniques, photoluminescence spectroscopy, electrochemical atomic force microscopy, and photocurrent measurement. The synthesized g‐C3 N4 NSs/TNTAs samples shows enhanced photocatalytic efficiency for rhodamine B degradation under visible light, which is four times more than that of pure TNTAs. Tetracycline hydrochloride could also be effectively degraded under visible light, which contributes to reducing antibiotic residues in wastewater. Additionally, g‐C3 N4 NSs/TNTAs also possess other advantages such as well long‐term stability and easily recyclable properties. A reaction mechanism is also proposed. Abstract : Light catalysis : An all‐solid‐state Z‐scheme photocatalytic system is constructed by immobilizing g‐C3 N4 nanosheets on TiO2 nanotube arrays. The g‐C3 N4 nanosheets/TiO2 nanotube arrays display prominent performances in degradation of the dye rhodamine B and the antibiotic tetracycline hydrochloride under visible light.